Aller au cinéma pour apprendre à être « moderne » ? - Anne Kerlan (Conserveries Mémorielles)
Movie at its beginnings in China took over many places traditionally dedicated to Chinese culture (teahouse, gardens, theater and opera houses); however, it became very quickly obvious that movie screenings should be held in places that could mirror the novelty of the show, either by the architecture, the design of the room or by the etiquette. This was particularly true for theaters where western films were screened: going to see such films could be conceived as a global experience, a way to learn in all aspects the western modernity carried by these products. This article explains, through the study of a very special movie theater, the True Light Theater (Zhenguang xiyuan), how Beijing moviegoers borrowed the new, western etiquette of the cinematographic shows. At the True Light, the manager introduced new rules of behavior that were modeled from an etiquette supposedly coming from the western movie theater. However, I will also explore how, if the True Light Theater was a place to experience the western modernity, Beijiners also locally adapted these news practices.